Predicting Posttraumatic Stress Symptoms Following Mild, Moderate, and Severe Traumatic Brain Injury. Issue 4 (July 2015) - Al-Ozairi, Abdullah; McCullagh, Scott; Feinstein, Anthony; Bushnik, Tamara; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Objective: To explore the relation between posttraumatic amnesia (PTA) and posttraumatic stress symptoms in traumatic brain injury. Design: Single-site prospective cohort study. Participants: A total of 1114 individuals between the ages of 18 and 65 years with a traumatic brain injury seen on average 3 months following injury. Participants were divided into 4 groups according to their duration of PTA: less than 1 hour; 1 to 24 hours; 24 hours to 1 week; and more than 1 week. Main Measures: Glasgow Coma Scale, PTA, computed tomographic brain scan abnormalities, Impact of Event Scale, the 28-item General Health Questionnaire, and Rivermead Postconcussion Disorder Questionnaire. Results: The duration of PTA less than 1 hour was associated with more avoidant (P < .01) and intrusive (P < .001) posttraumatic stress symptoms and more anxiety according to the General Health Questionnaire (P < .01) than other groups. Regression analysis identified PTA and 3 concussive symptoms (light sensitivity, noise intolerance, and difficulties concentrating) as independent predictors of intrusive posttraumatic stress symptoms. Conclusion: Our data, representative of the full range of traumatic brain injury severity, indicate that a brief duration of PTA is a significant risk factor for the development of posttraumatic stress disorder symptoms. The persistence of certain symptoms of postconcussion disorder adds to the risk by possibly acting as a trigger for reminders of the traumatic event.